2001
DOI: 10.1093/aje/154.11.1020
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Typhimurium Infections Transmitted by Chlorine-pretreated Clover Sprout Seeds

Abstract: Raw seed sprouts have caused numerous outbreaks of enteric infections. Presoaking seeds in a 20,000 mg/liter (ppm) calcium hypochlorite solution before sprouting is recommended to reduce bacterial contamination and infection risk. In 1999, the authors investigated an outbreak of Salmonella serotype Typhimurium infections in Colorado. In a case-control study, they matched 20 cases with 58 controls by age, sex, and telephone prefix; 10 (52%) of 19 cases and no controls recalled eating raw alfalfa-style sprouts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Relevant literature was grouped into two main subject categories: growth of pathogens during sprouting (1,8,16,19,33,41,42,47,49) and pathogen detection on seeds or sprouts (8,15,20,21,23,36,45,48,55,59). Epidemiological literature was reviewed to assemble a comprehensive understanding of primary risk factors in the sprouting process (3,4,9,25,29,30,35,37,52,53,58). Data on processes not currently used in sprouting operations were not included in our model (10, 12, 13, 18, 27, 34, 38, 39, 42-44, 54, 56).…”
Section: Methodsmentioning
confidence: 99%
“…Relevant literature was grouped into two main subject categories: growth of pathogens during sprouting (1,8,16,19,33,41,42,47,49) and pathogen detection on seeds or sprouts (8,15,20,21,23,36,45,48,55,59). Epidemiological literature was reviewed to assemble a comprehensive understanding of primary risk factors in the sprouting process (3,4,9,25,29,30,35,37,52,53,58). Data on processes not currently used in sprouting operations were not included in our model (10, 12, 13, 18, 27, 34, 38, 39, 42-44, 54, 56).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, strains that were serotyped as Newport by PFGE in the prior study were frequently MDR, while no MDR Newport strains were identified by rep-PCR in our study. Montevideo and Newport have been identified in several multistate outbreaks associated with fresh produce (4,6,37,49), while Hadar was more associated with meat or poultry (50,51). Strains with genetic similarity to serotypes Saintpaul, Braenderup, Thompson, and Javiana have also been recovered in produce-related outbreaks (6,42,(52)(53)(54), and Javiana is the most commonly reported serotype for salmonellosis in Florida (Carina Blackmore, Florida Department of Health, personal communication).…”
Section: Figmentioning
confidence: 99%
“…Epidemiological evidence suggests that this sanitation protocol may prevent some, but not all, outbreaks (2,5), and experimental sanitation of naturally contaminated alfalfa seeds did not eliminate S. enterica from the seeds (23). To date, no seed sanitation method has been shown to eliminate S. enterica or E. coli O157:H7 from laboratory-contaminated seeds (4,13,14,19,24,25).…”
mentioning
confidence: 99%